Selective Propagation of Pulse Packets in Feedforward Neuronal Networks by Including Resonance Pair - Chen, Yu-Qian; Si, Hao; Sun, Xiao-Juan (Journal of Applied Nonlinear Dynamics, 2026)
It has been shown that both periodic pulse packets and single pulse packet can be propagated in feedforward neuronal networks by including resonance pair. Based on these results, we further study the selective propagation of pulse packets in such feedforward neuronal networks. The obtained results show that periodic pulse packets can be propagated selectively when their periods match the network frequency, which can be controlled by background input, connection strength, and intra-layer connection probability. The relationship between these control parameters and network frequencies suggests that neuronal networks may adaptively change their states by modulating some parameters in order to selectively propagate signals.